Photo-responsive evaluation of solution-processed self-driven visible-blind NiO/ZnO/FTO photodetector - Ali H. Al-Beayaty, Mohammed; A. Dhahir, Abdal Kareem; Abdulghafor Ahmed, Maryam (Al-Nahrain Journal of Science, 2025)
In this article, the fabrication procedure of solution-processed NiO/ZnO/FTO heterostructure is systematically elucidated for self-driven visible-blind photodetector application. In detail, the opto-electrical analysis was investigated under multi-illumination wavelength of 375 nm, through which a linear dependency between the photocurrent ( ) and the incident intensity was perceived along a close to unity Pearson correlation coefficient ( ). The proposed heterojunction (p-NiO/n-ZnO) exhibited short-circuit current and open-circuit voltage of 4 µA and 0.8 V, which in turn validates the self-powered feature of the proposed geometry. The attained photo-responsivity ( ) and photo-detectivity ( ) exhibited values of 25.6 mA/W and 16.3 Jones, respectively, under light intensity of 17 mW/cm2. This was noticed along with considerable ( ) reduction near the visible light region. In conjunction, p-NiO/n-ZnO heterostructure demonstrated UV/vis rejection ratio ( ) of 572; other considered geometries (NiO/FTO and ZnO/FTO) revealed considerably lower ratios. At zero bias, the addressed junction demonstrated response/recovery times of 0.175 and 0.178 sec., respectively.